Martensitic steel and preparation method thereof

By optimizing the alloy composition and heat treatment process of martensite steel, tempered martensite structure and a small amount of M7C3 precipitation phase are formed, which solves the problem of the deterioration of toughness of martensite wear-resistant steel when increasing hardness, and achieves high wear resistance and excellent comprehensive mechanical properties.

CN119753529AActive Publication Date: 2025-04-04SOUTHWEST JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510063723.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

When existing martensite wear-resistant steels increase hardness and improve wear resistance, they can easily lead to deterioration of toughness, easily lead to brittle fracture, and reduce safety of use.

Method used

By optimizing the alloy composition and heat treatment process of martensite steel, the mass percentage of chemical elements is controlled, such as C 0.3 to 0.6 wt%, Mn 2 to 2.6 wt%, Cr 0.3 to 0.7 wt%, etc., combined with low-temperature tempering and quenching treatment, tempered martensite structure and a small amount of M7C3 precipitation phase are formed.

Benefits of technology

While improving wear resistance, the comprehensive mechanical properties of martensite steel are improved, good toughness is maintained, the hardness and tensile strength of the material are enhanced, and the safety of use is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753529A_ABST
    Figure CN119753529A_ABST
Patent Text Reader

Abstract

The invention discloses martensitic steel and a preparation method thereof, and belongs to the technical field of metal materials. The martensitic steel provided by the invention comprises the following chemical elements in percentage by mass: 0.3 to 0.6 weight percent of C, 2 to 2.6 weight percent of Mn, 0.3 to 0.7 weight percent of Cr, 0.05 to 0.2 weight percent of Ni, 0.4 to 0.8 weight percent of Mo, 1.3 to 1.7 weight percent of Si, 0.05 to 0.2 weight percent of V, 1 to 1.5 weight percent of Al and the balance of iron and inevitable impurities. The invention further provides a preparation method of the martensitic steel. The preparation method comprises the steps of smelting, forging, austenitizing, quenching and aging treatment. Alloy components and a preparation process of the martensitic steel are optimally designed, so that the martensitic steel has better wear resistance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials, and in particular relates to a martensitic steel and a preparation method thereof. Background Art

[0002] For a long time, the wear resistance of basic parts in my country is significantly lower than that of advanced foreign products. In recent years, my country's wear-resistant steel technology has made great progress. Medium and thick plate mills such as Wuhan Iron and Steel, Anshan Iron and Steel, Baosteel, Wuyang, and Taiyuan Iron and Steel can stably supply wear-resistant steel plates with a hardness level below HB400, and some manufacturers can produce wear-resistant steel plates with a strength level below HB500. At present, wear-resistant steel plates with a strength level above HB400 are still mainly imported. There is still a big gap between the strength level and performance of my country's wear-resistant steel products and foreign products.

[0003] Martensitic wear-resistant steel has become the first choice of wear-resistant steel due to its high strength and high strength. At the same time, martensitic wear-resistant steel has been widely used in coal mining, rail transportation and engineering machinery due to its simple manufacturing process, low material cost and excellent and stable mechanical properties. Hardness is the rating standard of martensitic wear-resistant steel, which can effectively affect the wear rate of martensitic wear-resistant steel. As the hardness of the matrix increases, the wear resistance of the material also increases. However, the hardness and toughness of the material generally have an inverted relationship, that is, increasing the hardness will cause the toughness of the material to decrease significantly, which is easy to cause brittle fracture of the wear-resistant steel during service, greatly reducing the safety of use. At the same time, under the same hardness conditions, the better the toughness of the wear-resistant material, the higher its wear resistance. Through certain element selection, content adjustment and optimization of heat treatment process, it is expected to improve the comprehensive mechanical properties of martensitic wear-resistant steel while improving its wear performance. Therefore, it is of great research significance and industrial application value to explore the mechanism of the composition and heat treatment process of martensitic steel on its mechanical properties and wear resistance, and to develop high wear-resistant martensitic steel with excellent comprehensive mechanical properties. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a martensitic steel and a preparation method thereof, which optimizes the alloy composition and heat treatment process of the martensitic steel, improves the wear resistance of the material and enhances its comprehensive mechanical properties.

[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: to provide a martensitic steel, the mass percentage of chemical elements is: C 0.3-0.6wt%, Mn 2-2.6wt%, Cr 0.3-0.7wt%, Ni0.05-0.2wt%, Mo0.4-0.8wt%, Si 1.3-1.7wt%, V 0.05-0.2wt%, Al 1-1.5wt%, and the balance is iron and inevitable impurities.

[0006] The beneficial effects of the present invention are as follows: in the high wear-resistant martensitic steel of the present invention, the carbon element directly affects the organizational morphology of the quenched martensite and the amount of carbide precipitation in the martensitic wear-resistant steel, thereby affecting the strength and plastic toughness. It is generally believed that the solid solution strengthening of carbon atoms is the main reason for carbon to improve strength in martensite. With the increase of carbon content, the more carbon dissolved in martensite, the higher the strength and the decrease of toughness. In low-carbon martensitic steel, martensite mainly exists in the form of laths. Due to its uniform distribution of carbides and relatively weak solid solution strengthening caused by low carbon, it has better plasticity. In medium-carbon steel, martensite exists in the form of flakes and laths. Combined with the heat treatment process of low-temperature tempering, it can significantly improve the strength without sacrificing plasticity excessively, thereby having relatively excellent comprehensive mechanical properties. Therefore, the C content is controlled to be 0.3-0.6wt% after comprehensive consideration.

[0007] Manganese can be dissolved in ferrite or austenite in martensitic wear-resistant steel to improve the strength and hardness of the steel. Manganese can significantly reduce the pearlite transformation temperature and make the C curve of the steel move strongly to the right, so the critical quenching rate is reduced, showing good hardenability, which is conducive to the transformation of steel to bainite and martensite. However, as the manganese content increases, it will cause intragranular segregation and center segregation, resulting in a significant decrease in plastic toughness. Therefore, the Mn content is controlled to be 2-2.6wt% after comprehensive consideration.

[0008] Chromium has similar effects to manganese in terms of solid solution strengthening, shifting the C curve to the right, reducing the martensitic transformation point Ms, and increasing hardenability, but it also has many advantages that manganese does not have. For example, chromium has good tempering resistance, corrosion resistance and oxidation resistance; at the same time, chromium can also form a continuous solid solution with iron and form a variety of complex carbides with carbon, such as M7C3 type carbides, which can improve the strength and hardness of martensitic wear-resistant steel, thereby improving its wear resistance. Therefore, considering comprehensive considerations, the Cr content is controlled to be 0.3-0.7wt%.

[0009] Nickel exists in the form of solid solution in the α phase and γ phase in steel, which can play a role in solid solution strengthening; at the same time, it does not form carbides with carbon, and is the main alloying element for forming and stabilizing austenite, which can improve the plasticity and toughness of martensitic wear-resistant steel. However, nickel is relatively scarce, and adding more is not conducive to cost control. Therefore, the content of Ni is controlled to 0.05-0.2wt% after comprehensive consideration.

[0010] Molybdenum can improve the hardenability of steel, promote the formation of martensitic structure, and prevent temper brittleness. At the same time, molybdenum improves the plasticity, toughness and impact resistance of martensitic wear-resistant steel by refining grains and inhibiting grain boundary embrittlement. However, molybdenum is a precious metal and is expensive. The synergistic effect with Cr and Ni elements must be considered in the design. Therefore, the Mo content is controlled to be 0.4-0.8wt% after comprehensive consideration.

[0011] Silicon is easily dissolved in ferrite to play a role in solid solution strengthening. It can also dissolve in cementite, making cementite unstable and hindering its precipitation and segregation. At the same time, silicon will also delay the transformation of carbide to cementite, increasing the temperature range of low-temperature temper brittleness, thereby improving tempering resistance. However, if the silicon content is too high, quenching cracks are likely to occur and temper brittleness is increased. Therefore, the Si content is controlled to 1.3-1.7wt% after comprehensive consideration.

[0012] Vanadium can improve the hardenability of martensitic wear-resistant steel and enhance the dispersion and precipitation of carbides; at the same time, it refines the grains and inhibits grain growth, improving the strength, hardness, impact toughness and wear resistance of the material. However, excessive addition of vanadium will significantly deteriorate the processing performance of martensitic wear-resistant steel. Therefore, considering comprehensive considerations, the V content is controlled to be 0.05-0.2wt%.

[0013] The addition of aluminum can significantly reduce the density of the material, making it lightweight; at the same time, it refines the grains and improves the strength and hardness of the material. Therefore, the aluminum content is controlled to be 1-1.5wt% after comprehensive consideration.

[0014] Elements such as C, Mn, Cr, and Ni dissolve into the Fe matrix, causing lattice distortion, thereby improving the strength and hardness of steel. Elements such as Mn, Cr, Ni, and Mo improve the hardenability of steel, and affect the transformation of austenite to martensite by expanding the austenite zone and reducing the critical transformation temperature after quenching. The combination of Ni and Si promotes the uniform nucleation of the precipitated phase, improving the plastic deformation ability and toughness of steel.

[0015] Based on the above technical solution, the present invention can also be improved as follows.

[0016] Further, the mass percentages of chemical elements are: C 0.46wt%, Mn 2.3wt%, Cr 0.49wt%, Ni0.09wt%, Mo 0.68wt%, Si 1.5wt%, V 0.08wt%, Al 1.12wt%, and the balance is iron and inevitable impurities.

[0017] The beneficial effect of adopting the further technical solution is: optimizing the mass percentage of chemical components to obtain martensitic steel with excellent comprehensive properties.

[0018] Furthermore, the microstructure of the martensitic steel is as follows: 95% to 97% of tempered martensitic structure and 3% to 5% of M7C3 precipitation phase in volume percentage.

[0019] The beneficial effect of adopting a further technical solution is that the M7C3 precipitation phase (M7C3 carbide) is evenly distributed in the martensite structure, effectively hindering the dislocation movement and thus enhancing the strength and hardness of the material. Under appropriate heat treatment conditions, such as tempering after austenitization, M7C3 carbides can undergo precipitation hardening and secondary hardening, increasing the hardness and tensile strength of the material. This strengthening effect mainly comes from the strengthening effect of carbides on the matrix structure; but excessive precipitation or improper heat treatment process may also lead to a decrease in the toughness of the material. Therefore, while pursuing high strength and high hardness, controlling the volume percentage content of 3% to 5% maintains the good toughness of martensitic steel.

[0020] The present invention also discloses a method for preparing martensitic steel, comprising the following steps:

[0021] S1: preparing raw materials according to the mass percentage of chemical elements, smelting and forging the raw materials to obtain billet 1;

[0022] S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to Ac3 temperature to Ac3 temperature + 50°C at a rate of 15-25°C / min, and kept warm for 5-25min to obtain billet 2;

[0023] S3: After quenching the blank 2, cool it to room temperature to obtain the blank 3;

[0024] S4: heating the billet 3 to 150-200°C at a rate of 15-25°C / min, keeping the temperature for 3-7h, and then air-cooling to room temperature to obtain martensitic steel.

[0025] Further, the steps of smelting and forging are:

[0026] S1: Put the raw materials into an electric arc furnace and melt them into molten steel at 1630-1700℃;

[0027] S2: pouring the molten steel into a refining device and refining the molten steel at 1620°C and in an inert gas atmosphere;

[0028] S3: pouring the refined molten steel into a vacuum device for degassing;

[0029] S4: Pour the degassed molten steel into the crystallizer of the continuous casting machine, and obtain billet 1 after cooling.

[0030] Furthermore, the Ac3 temperature is 844°C.

[0031] Furthermore, the quenching method is water quenching.

[0032] Furthermore, the air cooling rate was 20°C / min.

[0033] The beneficial effect of the preparation method of the present invention is that the austenitizing holding time of the preparation method provided by the present invention is short, which can avoid the original austenite grains being too coarse due to the holding time being too long, affecting the martensite structure obtained after quenching, and then deteriorating the comprehensive mechanical properties of the martensitic steel, and then quenching to room temperature to obtain a full martensite structure; then heating to 185°C for low-temperature tempering again to avoid the occurrence of M 23 C6 and other precipitation phases that deteriorate the comprehensive mechanical properties of the material, and at the same time, different tempering times are used to obtain martensitic steels with different hardness, strength, and plastic toughness, and finally air-cooled to room temperature at a rate of 15-25°C / s to obtain tempered martensitic structure and a small amount of M7C3 precipitation phase. This method optimizes the steps of austenitization, quenching and tempering in the preparation of martensitic steel in the prior art. The microstructure of the obtained martensitic steel is tempered martensitic structure + a small amount of M7C3 precipitation phase. The M7C3 precipitation phase can significantly enhance the hardness and strength of martensitic steel, thereby improving its wear resistance, so this method has excellent industrial prospects.

[0034] The beneficial effect of the present invention is as follows: the present invention optimizes the alloy composition and heat treatment preparation process of martensitic steel so that the microstructure of the obtained martensitic steel is tempered martensitic structure + a small amount of M7C3 precipitation phase, so that it has better wear performance, while improving the wear resistance and comprehensive mechanical properties, thereby obtaining a wear-resistant steel with excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the preparation flow chart of martensitic steel;

[0036] Figure 2 This is the scanning electron microscope micrograph of the martensitic steel prepared in Example 1. DETAILED DESCRIPTION

[0037] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0038] Example 1

[0039] A martensitic steel, wherein the chemical elements are as follows: C 0.46wt%, Mn 2.3wt%, Cr 0.49wt%, Ni 0.09wt%, Mo 0.68wt%, Si 1.5wt%, V 0.08wt%, Al 1.12wt%, and the remainder is iron and inevitable impurities.

[0040] The above martensitic steel is prepared by the following steps (such as Figure 1 As shown) to obtain:

[0041] S1: raw materials are prepared according to the mass percentage of chemical elements, the raw materials are put into an electric arc furnace to be melted into molten steel at 1650°C, the molten steel is then poured into an LF furnace for refining at 1620°C under argon atmosphere, the refined molten steel is then poured into a VD vacuum furnace for degassing, and finally the degassed molten steel is poured into a crystallizer of a continuous casting machine, and billet 1 is obtained after cooling;

[0042] S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to 885° C. at a rate of 20° C. / min and kept at this temperature for 15 min to obtain billet 2;

[0043] S3: After quenching the second blank, cooling it to room temperature, obtaining the third blank;

[0044] S4: Billet 3 was heated to 185°C at a rate of 20°C / min, kept at that temperature for 5 hours, and then air-cooled to room temperature at a rate of 20°C / min to obtain martensitic steel.

[0045] Example 2

[0046] A martensitic steel, wherein the chemical elements are as follows in percentage by weight: C 0.3wt%, Mn 2.6wt%, Cr 0.3wt%, Ni 0.2wt%, Mo 0.4wt%, Si 1.7wt%, V 0.05wt%, Al 1.5wt%, and the remainder is iron and inevitable impurities.

[0047] The above martensitic steel is prepared by the following steps (such as Figure 1 As shown) to obtain:

[0048] S1: raw materials are prepared according to the mass percentage of chemical elements, the raw materials are put into an electric arc furnace to be melted into molten steel at 1630°C, the molten steel is then poured into an LF furnace for refining at 1620°C under argon atmosphere, the refined molten steel is then poured into a VD vacuum furnace for degassing, and finally the degassed molten steel is poured into a crystallizer of a continuous casting machine, and billet 1 is obtained after cooling;

[0049] S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to 894° C. at a rate of 15° C. / min and kept at this temperature for 5 min to obtain billet 2;

[0050] S3: After quenching the second blank, cooling it to room temperature, obtaining the third blank;

[0051] S4: Billet 3 was heated to 150°C at a rate of 15°C / min, kept at that temperature for 7 hours, and then air-cooled to room temperature at a rate of 15°C / min to obtain martensitic steel.

[0052] Example 3

[0053] A martensitic steel, wherein the chemical elements are as follows in percentage by weight: C 0.6wt%, Mn 2wt%, Cr 0.7wt%, Ni 0.05wt%, Mo 0.8wt%, Si 1.3wt%, V 0.2wt%, Al 1.wt%, and the balance is iron and inevitable impurities.

[0054] The above martensitic steel is prepared by the following steps (such as Figure 1 As shown) to obtain:

[0055] S1: raw materials are prepared according to the mass percentage of chemical elements, the raw materials are put into an electric arc furnace to be melted into molten steel at 1700°C, the molten steel is then poured into an LF furnace for refining at 1620°C in an argon atmosphere, the refined molten steel is then poured into a VD vacuum furnace for degassing, and finally the degassed molten steel is poured into a crystallizer of a continuous casting machine, and billet 1 is obtained after cooling;

[0056] S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to 885°C at a rate of 25°C / min and kept at this temperature for 25 minutes to obtain billet 2;

[0057] S3: After quenching the second blank, cooling it to room temperature, obtaining the third blank;

[0058] S4: Billet 3 is heated to 200°C at a rate of 25°C / min, kept at that temperature for 3h, and then air-cooled to room temperature at a rate of 25°C / min to obtain martensitic steel.

[0059] Comparative Example 1

[0060] The commercial martensitic wear-resistant steel NM400 in the prior art.

[0061] Comparative Example 2

[0062] The commercial martensitic wear-resistant steel NM500 in the prior art.

[0063] Comparative Example 3

[0064] A martensitic steel, wherein the chemical elements are as follows: C 0.148wt%, Mn 1.884wt%, Cr 0.176wt%, Ni 0.015wt%, S 0.019wt%, Si 0.204wt%, V 0.0022wt%, Nb 0.0005wt%, and the remainder is iron and inevitable impurities.

[0065] The above martensitic steel is prepared by the following steps (such as Figure 1 As shown) to obtain:

[0066] S1: raw materials are prepared according to the mass percentage of chemical elements, the raw materials are put into an electric arc furnace to be melted into molten steel at 1650°C, the molten steel is then poured into an LF furnace for refining at 1620°C under argon atmosphere, the refined molten steel is then poured into a VD vacuum furnace for degassing, and finally the degassed molten steel is poured into a crystallizer of a continuous casting machine, and billet 1 is obtained after cooling;

[0067] S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to 885° C. at a rate of 20° C. / min and kept at this temperature for 15 min to obtain billet 2;

[0068] S3: After quenching the second blank, cooling it to room temperature, obtaining the third blank;

[0069] S4: Billet 3 was heated to 185°C at a rate of 20°C / min, kept at that temperature for 5 hours, and then air-cooled to room temperature at a rate of 20°C / min to obtain martensitic steel.

[0070] Comparative Example 4

[0071] A martensitic steel, wherein the chemical elements are as follows: C 0.46wt%, Mn 2.3wt%, Cr 0.49wt%, Ni 0.09wt%, Mo 0.68wt%, Si 1.5wt%, V 0.08wt%, Al 1.12wt%, and the remainder is iron and inevitable impurities.

[0072] The above martensitic steel is prepared by the following steps (such as Figure 1 As shown) to obtain:

[0073] S1: raw materials are prepared according to the mass percentage of chemical elements, the raw materials are put into an electric arc furnace to be melted into molten steel at 1650°C, the molten steel is then poured into an LF furnace for refining at 1620°C under argon atmosphere, the refined molten steel is then poured into a VD vacuum furnace for degassing, and finally the degassed molten steel is poured into a crystallizer of a continuous casting machine, and billet 1 is obtained after cooling;

[0074] S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to 1245° C. at a rate of 12° C. / min and kept at this temperature for 15 min to obtain billet 2;

[0075] S3: After quenching the second blank, cooling it to room temperature, obtaining the third blank;

[0076] S4: Billet 3 was heated to 230°C at a rate of 30°C / min, kept at that temperature for 300s, and then air-cooled to room temperature at a rate of 25°C / min to obtain martensitic steel.

[0077] Experimental Example 1

[0078] Metallographic characterization experiment: The martensitic steel prepared in Example 1 was observed using a scanning electron microscope. Figure 2 As shown, the microstructure is statistically 96% tempered martensite and 4% M7C3 precipitation phase by volume percentage; the martensitic steels prepared in Examples 2 and 3 are also observed, and the microstructure of Example 2 is 95% tempered martensite and 5% M7C3 precipitation phase by volume percentage; the microstructure of Example 3 is 97% tempered martensite and 3% M7C3 precipitation phase by volume percentage.

[0079] Experimental Example 2

[0080] Performance test: The martensitic steels prepared in Examples 1 to 3, the commercial martensitic wear-resistant steels NM400 and NM500 of Comparative Examples 1 to 2, and the martensitic steels prepared in Comparative Examples 3 to 4 were tested for performance in the following manner:

[0081] The wear test was carried out on a high-precision reciprocating friction and wear testing machine using a ball-plane contact method. The wear specimens were processed into 15mm×10mm×2mm, and the specimens were ground and polished to a mirror surface (Ra 0.02μm) before the test. Si3N4 ceramic balls with a hardness of 1500HV and a diameter of 3mm were selected as the grinding pair material. All specimens and Si3N4 balls were ultrasonically cleaned and dried in alcohol for 15 minutes before the wear test to ensure that there were no contaminants on the surface of the specimens. The friction tests were carried out in atmospheric and room temperature environments with a relative humidity of 50% to 60%, a displacement amplitude of 2500μm, normal loads of 10N and 30N respectively, an experimental frequency of 2Hz, and a cycle of 1×10 4 After the wear test, a white light interferometer (Bruker GTK-16-0295) was used to quantitatively characterize the wear spot profile and wear volume to analyze the wear performance of the alloy steel. In order to avoid irregular shapes at both ends of the wear scar and ensure the reliability of the experimental data, each group of tests was repeated three times, and the wear volume was only taken from the 4mm area in the middle of the wear scar, and its numerical value was used as the evaluation index of wear resistance.

[0082] The indentation load of the hardness test was set to 200gN, and the holding time was 15s. Before the test, the sample needs to be ground and polished to obtain a flat and uniform test surface. To ensure the accuracy of the test results, 10 points are measured for each sample and the average value is taken as the final hardness value. In the tensile test, the tensile rate is set to 1.5mm / min, and the sample tensile test is carried out in accordance with the ASTM (E-8) standard. The thickness is 2mm, and the tensile direction of the sample is parallel to the hot rolling direction. The total elongation is measured using an extensometer with a gauge length of 25mm, and the maximum displacement of the extensometer is taken as the total elongation, which can maximize the accuracy of the tensile data curve. In order to reduce the random error of the experiment, the tensile test was repeated three times, and the average value was taken as the value of each mechanical property.

[0083] The test results are shown in Table 1. The martensitic steel provided by the present invention (Examples 1 to 3) has better wear resistance than the existing commercial martensitic wear-resistant steels NM400 and NM500 and the martensitic steels of Comparative Examples 3 to 4, and at the same time has more excellent comprehensive mechanical properties.

[0084] Table 1 Performance test results

[0085]

[0086]

[0087] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A martensitic steel, characterized in that: The mass percentages of the chemical elements are: C 0.3-0.6wt%, Mn 2-2.6wt%, Cr 0.3-0.7wt%, Ni 0.05-0.2wt%, Mo 0.4-0.8wt%, Si 1.3-1.7wt%, V0.05-0.2wt%, Al 1-1.5wt%, and the balance is iron and inevitable impurities.

2. The martensitic steel according to claim 1, characterized in that: The mass percentages of chemical elements are: C 0.46wt%, Mn 2.3wt%, Cr 0.49wt%, Ni 0.09wt%, Mo 0.68wt%, Si 1.5wt%, V 0.08wt%, Al 1.12wt%, and the balance is iron and inevitable impurities.

3. The martensitic steel according to claim 1, characterized in that: The microstructure of the martensitic steel comprises, by volume percentage, 95% to 97% of tempered martensitic structure and 3% to 5% of M7C3 precipitation phase.

4. The method for preparing martensitic steel according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: raw materials are prepared according to the mass percentage of chemical elements, and the raw materials are smelted and forged to obtain billet 1; S2: After hot rolling the billet 1 to a thin plate steel with a thickness of 2 mm, the thin plate steel is heated to Ac3 temperature to Ac3 temperature + 50°C at a rate of 15-25°C / min, and kept warm for 5-25min to obtain billet 2; S3: After quenching the blank 2, cool it to room temperature to obtain the blank 3; S4: heating the billet 3 to 150-200°C at a rate of 15-25°C / min, keeping the temperature for 3-7h, and then air-cooling to room temperature to obtain martensitic steel.

5. The method for preparing martensitic steel according to claim 4, characterized in that: The steps of smelting and forging are: S1: Put the raw materials into an electric arc furnace and melt them into molten steel at 1630-1700℃; S2: pouring the molten steel into a refining device and refining the molten steel at 1620°C and in an inert gas atmosphere; S3: pouring the refined molten steel into a vacuum device for degassing; S4: Pour the degassed molten steel into the crystallizer of the continuous casting machine, and obtain billet 1 after cooling.

6. The method for preparing martensitic steel according to claim 4, characterized in that: The Ac3 temperature is 844°C.

7. The method for preparing martensitic steel according to claim 4, characterized in that: The quenching method is water quenching.

8. The method for preparing martensitic steel according to claim 4, characterized in that: The air cooling rate is 20°C / min.

Citation Information

Patent Citations

  • Martensite series wear-resistant steel and preparation method thereof

    CN103397275A

  • Carbide-containing high-strength high-toughness bainite wear-resistant steel and preparation method thereof

    CN112695253A

  • Low-cost high-strength wear-resistant steel with nano bainite structure and preparation method of low-cost high-strength wear-resistant steel

    CN116770177A

  • Bainite / martensite complex-phase wear-resistant steel and heat treatment method thereof

    CN116875876A

  • Clad hot-rolled and cold-rolled steel sheet, presenting a very high resistance after thermal treatment

    EP0971044A1